Treatment of complicated bacterial pneumonia in children (Research, Society and Development, 2024)
Introduction: Community-acquired pneumonia (CAP) is one of the most common infectious diseases in pediatrics, and may be related to the direct occurrence of local complications such as empyema, necrotizing pneumonia, lung abscess or pleural effusion, which are directly related to worsening of the clinical aspect and prolongation of the hospitalization period. Methodology: A narrative review of the literature was carried out in the PUBMED database, using the following keywords: “Bacterial pneumonia in children”, “Complicated Pneumonia” and “Treatment”, with the time filter for the last 5 years (2019-2023). Results: From the research carried out, 408 articles were identified, of which, after applying inclusion and exclusion criteria, 12 were selected for analysis. Discussion: The main complications are related to specific complementary exams and assertive surgical or antimicrobial therapies that seek to avoid mortality, exacerbation of other complications and reduce hospitalization time and associated morbidities. Conclusion: Knowledge about the complications of community-acquired pneumonia, particularly its course of development and its propaedeutic approach, helps to alleviate the difficulties of the clinical context and provide more security to the doctor in his/her healthcare assistance to the patient.